Unlocking success: factors influencing zakat collection and reputation at Indonesian zakat institution - Amar, Faozan; Purwoko, Bambang; Sihite, Mombang (Indonesian Journal of Islam and Muslim Societies, 2024)
This study aims to determine the factors that influence the increase in zakat collection and institutional reputation at the Muhammadiyah Zakat Infaq and Shadaqah Institution (LAZISMU). The variables studied are Digital Fundraising, Organizational Capability, Religiosity as independent variables. Increased collection as the dependent variable and institutional reputation as the mediating variable. The sample used was 249 respondents from the western, central and eastern Indonesian regions. Data analysis techniques using Structural Equation Model (SEM) techniques with the help of Smart PLS 4 statistical tools. The results showed that digital fundraising, organizational capabilities have a positive and significant influence on increasing zakat collection and institutional reputation. Religiosity has a positive and significant influence on increasing zakat collection. However, it has no influence on institutional reputation. The mediation results show that institutional reputation mediates the relationship between digital fundraising, organizational capability, religiosity to the increase in zakat collection. The implication of this research is that to obtain the level of trust of muzakki to pay professional zakat, it is necessary to pay attention to good institutional management and adequate personnel support so as to increase the collection of zakat and institutional reputation.